2015
DOI: 10.1097/hcm.0000000000000048
|View full text |Cite
|
Sign up to set email alerts
|

Value-Based Purchasing, Efficiency, and Hospital Performance

Abstract: The Medicare hospital value-based purchasing (HVBP) program that links Medicare payments to quality of care became effective in 2013 in the United States. Hospital efficiency will be added to the HVBP in 2015. It is unclear whether hospital efficiency-specific hospital characteristics are associated with HVBP performance scores and the subsequent incentive payments. Using data from the American Hospital Association Annual Survey the Medicare Hospital Compare, this article examines the association of hospital e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 10 publications
(11 reference statements)
0
23
0
Order By: Relevance
“…Private providers and providers with low baseline quality scores improved their performance the most (Hudson Health plan, MSSP, Pioneer ACO, QOF, VBP, VIP) [ 45 , 59 , 60 , 71 , 81 – 84 ], although some studies concerning the VBP report relatively poor performance of initially low-scoring providers, and in HQID safety net hospitals performed relatively poorly [ 9 , 61 63 , 67 , 79 , 80 ]. Among the narrow OBPMs, three models (HQID, Hudson Health plan, QOF) show that large providers outperform smaller ones [ 30 , 60 , 85 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Private providers and providers with low baseline quality scores improved their performance the most (Hudson Health plan, MSSP, Pioneer ACO, QOF, VBP, VIP) [ 45 , 59 , 60 , 71 , 81 – 84 ], although some studies concerning the VBP report relatively poor performance of initially low-scoring providers, and in HQID safety net hospitals performed relatively poorly [ 9 , 61 63 , 67 , 79 , 80 ]. Among the narrow OBPMs, three models (HQID, Hudson Health plan, QOF) show that large providers outperform smaller ones [ 30 , 60 , 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the narrow OBPMs, three models (HQID, Hudson Health plan, QOF) show that large providers outperform smaller ones [ 30 , 60 , 85 ]. In the VBP model, this scale effect is mixed [ 83 , 84 , 86 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research, as well as the descriptive statistics in Table 1, also suggested that hospitals with academic status were at a disadvantage. [13,20] Given these findings, academic hospitals, or other large hospitals that provide care for the underserved, or both, may be disadvantaged in the HVBP program.…”
Section: Discussionmentioning
confidence: 99%
“…It is also desirable that the technology be appealing and impressive to patients and their caregivers. 5,13,[17][18][19] Quality of outcome is not determined by merely asserting the novelty of an instrument or therapeutic modality. It is necessary to ask what incremental benefit might be expected relative to performance and cost of this technology when compared to competing products.…”
Section: The Business Of Ophthalmologymentioning
confidence: 99%